Physical education, sport and recreation: A triad pedagogy of hope - van Deventer , KJ (South African Journal of Higher Education, 2011)
Bloch (2009, 58), a previous advocate of Outcomes-based Education (OBE), states that schooling in SA is a national disaster. Quality holistic education that includes Physical Education (PE) and school sport should be the focal point of progress in developing countries. However, PE is worldwide in a political crisis and the situation is no different in South Africa (SA). Curriculum 2005 (C2005), the first democratic curriculum, launched a total onslaught on PE by drawing on unworkable proposals from New Zealand and Australia. Life Orientation (LO), a new Subject, which accommodates PE, came with C2005. Researchers found that within the context of transformation, LO are struggling to define itself. To determine the state of PE within the context of LO, a study was conducted in selected primary and secondary schools in the Eastern Cape (EC), Free State (FS) and North-West (NW) Provinces and compared with a study previously conducted in the Western Cape Province (WC). The findings indicated that most of the schools were located in previously disadvantaged areas and that 50 per cent of the LO teachers who facilitated PE in the four provinces were not qualified in PE. The United Nations (UN) view PE and sport as an important vehicle to achieve the Millennium Development Goals (MDGs). To contribute to the economic and social growth and improved public health, it is recommended that PE and school sport as very powerful transformative tools can enrich the lives of poor township learners as well as play a critical role in community upliftment.